2020
DOI: 10.3390/molecules25081873
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Crystallization Inhibitors for Salt Damage Control in Porous Materials: An Overview

Abstract: The use of inhibition chemicals holds the prospect of an efficient strategy to control crystallization in porous materials, thereby potentially contributing to the prevention or mitigation of the salt decay phenomenon in modern as well as historical building materials in a more sustainable manner. In this review, we first provide an essential background on the mechanism of salt crystallization and on the factors influencing this phenomenon; next, we illustrate the mechanism at the basis of the action of crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 117 publications
(235 reference statements)
0
18
0
Order By: Relevance
“…Porosimetry measurements indicates in fact that soll exhibits lower overall porosity compared to bajda and safra (29.8% vs. 30.4% and 35.6%, respectively). For the soll, the maximum concentration of distribution of pores is in the ranges 1-0.6 µm and 1-2 µm, whereas franka has a higher percentage of large pores (2-4 µm) [1,13,20]. Similarly, within the group of limestones from South Eastern Sicily, the somewhat different grouping for Noto and Palazzolo varieties (N and P, respectively) reflects small differences in terms of chemical composition (P limestone has a larger silicate component compared to N counterpart, i.e., 5.4% vs. 3.5%) and porous structure (P limestone exhibits a higher percentage (32.5%) of large pores (2-4 µm) relative to N (20.1%)) [14].…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Porosimetry measurements indicates in fact that soll exhibits lower overall porosity compared to bajda and safra (29.8% vs. 30.4% and 35.6%, respectively). For the soll, the maximum concentration of distribution of pores is in the ranges 1-0.6 µm and 1-2 µm, whereas franka has a higher percentage of large pores (2-4 µm) [1,13,20]. Similarly, within the group of limestones from South Eastern Sicily, the somewhat different grouping for Noto and Palazzolo varieties (N and P, respectively) reflects small differences in terms of chemical composition (P limestone has a larger silicate component compared to N counterpart, i.e., 5.4% vs. 3.5%) and porous structure (P limestone exhibits a higher percentage (32.5%) of large pores (2-4 µm) relative to N (20.1%)) [14].…”
Section: Resultsmentioning
confidence: 97%
“…It is generally understood as a temperature/humidity dependent weathering process arising from: (1) the presence of salt crystals on the surface of porous materials, which generally results in an aesthetic rather than mechanical damage (i.e., efflorescence), or (2) mechanical stresses introduced by salt crystals deposited within the material pores (i.e., sub-florescence or crypto-florescence), which may undermine the structural safety of the materials as well as cause widespread loss of (sometimes precious) surface. Despite having acquired significant knowledge of the decay mechanisms, several relative fundamental issues have not yet been fully understood [1][2][3]. Accordingly, adequate prevention or mitigation strategies are often lacking.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…was survival in UV exposure for 80 minutes. Other studies revealed to phages were fоund in envirоnments with high UV irradiation and heat as the Sahara ( Pachepsky et al, 2014) or hоt springs ( Percival et al, 2014) or in envirоnments with various pH values and ionic strengths like in food (Kausar and Qamer, 2016), cheese factories ( Bracciale et al, 2020), humans (Bach et al, 2005, soil ( Carla et al, 2020), and sewage (Iliadis et al, 2018). Moreоver, maintenance of phage pоpulations usually requires the presence of the bacterial hоst, which is alsо influenced by envirоnmental factоrs ( Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%